The effects of plant type, AMF inoculation and water regime on rhizosphere microbial communities. (14th October 2019) - Monokrousos, Nikolaos; Papatheodorou, Efimia M.; Orfanoudakis, Michael; Jones, Dylan‐Gwynn; Scullion, John; Stamou, George P.
Abstract: Different plant species, water regimes and microbes in the rhizosphere might shape rhizosphere microbial communities due to their effects on root exudation patterns and interactions. In this study, we investigated whether rhizosphere microbial communities have distinct structures according to plant type ( Festuca pratensis, Dactylis glomerata or a mixture of both species), water regime (dry and wet pots) and inoculation with the arbuscular mycorrhizal fungus Rhizophagus irregularis ( AMF). Following a 60‐day pot experiment we assessed the rhizosphere microbial population structure via phospholipid fatty acids (PLFAs) and soil processes via the activity of N ‐acetyl‐glucosaminidase (NAG), acid phosphatase and urease, and inorganic nitrogen (N) and phosphorus (P). Higher AMF colonization was recorded in F. pratensis, although its root and shoot biomass was lower than in D. glomerata . Although growth differed between the plant types, this exerted no influence on rhizosphere microbial biomass. Low water content decreased the biomass of all microbial groups, whereas inoculation with AMF decreased the biomass of fungi and increased that of bacteria. For enzyme activities only urease showed a response to treatments. Arbuscular mycorrhizal fungi inoculation increased available P and shifted mineral N content from nitrate to ammonium. The water regime had a dominant effect on the structure of the microbial communities, suggesting a direct effect of water on microbes. In wet soils, the structure of the microbial communities was modulated mainly by inoculation; AMF‐inoculated D. glomerata soils showed distinct communities. In dry soils, plant type exerted a profound effect on rhizosphere communities; the communities of all three plant types differed, probably due to limitations in the diffusion of nutrients or via reduced root exudation. We concluded that the relative importance of factors shaping rhizosphere microbial communities varies depending on soil moisture regime. Highlights: Microbial communities were studied in relation to water regime, plant species and AMF inoculation In wet soils, the microbial communities of AMF‐inoculated D. glomerata plants differed from other communities In dry soils, the microbial communities of D. glomerata and mixtures differed AMF increased bacterial biomass and soil P but decreased nitrate:ammonium ratio